2013
DOI: 10.1002/jor.22428
|View full text |Cite
|
Sign up to set email alerts
|

Inducible displacements of the cup and the femoral head during active range of motion: Dynamic RSA studies of cemented total hip replacements

Abstract: We evaluated changes in position of the femoral head relative to the cup and of the cup relative to the pelvis in total hip replacement patients during hip motion 2 years postoperatively. Two patient groups with nine patients in each group were studied. Hip motions, translations of the femoral head center, and cup displacements were recorded with dynamic radiostereometric examination (RSA, 2 exposures/s) during abduction in Group 1 and with use of static RSA exposures at increasing flexion of the hip in Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In other instances, too many bone markers were hidden behind the stem of the prostheses. Despite these drawbacks, we think that the data available can provide interesting information about the resolution of an OTS related to true skeletal motions performed by RSA …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other instances, too many bone markers were hidden behind the stem of the prostheses. Despite these drawbacks, we think that the data available can provide interesting information about the resolution of an OTS related to true skeletal motions performed by RSA …”
Section: Discussionmentioning
confidence: 99%
“…These authors used dynamic radiostereometric examination at two exposures/s. In contrast to our examination technique, active abduction was studied only weight‐bearing on the opposite leg to evaluate femoral head translations and cup displacements …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In THA patients, femoral head medio‐lateral translation has been observed during gait and non‐weight bearing activities . Komistek et al found an average 2.0 mm femoral head medio‐lateral translation during the swing phase of gait while Dennis et al found an average 3.3 mm femoral head medio‐lateral translation during active hip abduction.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that THA limits femoral head translations. However, this is a desirable effect of THA design in an attempt to decrease polyethylene wear and components loosening …”
Section: Discussionmentioning
confidence: 99%